Legal imperatives and mechanisms for protection of national interests in international investment activities - Flissak, Kostyantyn (Actual problems of law (Aktual'ni problemi pravoznavstva), 2026)
Investment activity is one of the cornerstones of socio-economic development of territories, countries, and regional formations, as well as one of the main criteria for classifying states as developed or developing. This topic has not lost its relevance for decades. The problems of investment, investment activities, and investment processes are constantly in the field of view of economists, scientists, practitioners, politicians, and statesmen. Long-term investment of capital, its movement between countries in the context of the international division of labour and globalization processes is one of the main factors for creating the necessary material potential for the development of the economy of the relevant countries. At the same time, cross-border capital movement characterizes the openness of national economies and confirms their market status.This process is a component of international economic relations and manifests itself in the form of capital exports. At the same time, there are differences in estimates and the impact of exports of goods and services on the formation of gross domestic product and capital exports for national economies. If the export of goods and services clearly has a positive impact, then the export of capital can be evaluated differently and have a different impact on national economies: on the one hand, it is the attraction of capital, in particular, foreign direct investment, on the other hand, it is the outflow of funds outside the country, and in some cases, the direct flight of capital. In such circumstances, a conflict of interest inevitably arises between states, individual enterprises that are subjects of investment activity, and multinational corporations.Thus, the problem of protecting national interests may become more acute. This makes it necessary to form and constantly develop appropriate mechanisms for guaranteeing investments and protecting them, that is, the problem of taking into account and developing the necessary imperatives for protecting national interests in investment activities, especially in the field of international economic relations, remains relevant. This applies not so much to economic levers of influence as to effective regulatory mechanisms at the national and international levels.Based on the above, the article considers the issue of the need to implement modern imperatives of protecting the national interests of states in the process of international capital movements and the form of direct investment, depending on the interest in attracting them to the national economy or in investing abroad. There is drawn attention to the fragmentation and grouping of countries depending on interest in transnational investment. Investment protection tools in the system of international investment law are investigated and the main criteria requirements for the actions of countries participating in the cross-border investment process are structured. Attention is focused on investment risks and investment threats to national interests and national security, the origin of which can be both internal and external. The article highlights the peculiarities of imperatives and mechanisms for protecting national interests in international investment activities of the European Union, the United States of America, the Federal Republic of Germany, Japan and India. There are formulated conclusions on the problems of international investment law in terms of actions aimed at investments protecting.